Analisis Banking Channel Terhadap Kepuasan Muzakki BAZNAS Jember - Jauhairina Galini; Uliyatul Mu’awwanah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Account transfer service, known as Banking Channel, is a service provided by the National Zakat Agency (BAZNAS) Jember, facilitating payments of Zakat, Infaq, and Shodaqoh through bank account transfers to BAZNAS Jember's designated account. This study aims to determine and analyze the impact of zakat account transfer services or Banking Channel on the satisfaction of muzakki (those who pay zakat) at BAZNAS Jember District. This research adopts a quantitative approach. Data collection method involves using questionnaires. Probability sampling is employed for sample selection, and the sample size is determined using the Slovin formula, resulting in 94 respondents. The analysis technique used is simple linear regression analysis. Based on the research findings, it is concluded that zakat account transfer services or Banking Channel significantly influence muzakki satisfaction at BAZNAS Jember. Hypothesis testing results indicate that the banking channel service (X) has a positive and significant effect on muzakki satisfaction at BAZNAS Jember (Y), confirming that the hypothesis regarding the banking channel service's impact on muzakki satisfaction at BAZNAS Jember is supported and accepted.